2020
DOI: 10.5588/ijtld.19.0526
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for pulmonary rehabilitation in chronic respiratory diseases in sub-Saharan Africa: a systematic review

Abstract: BACKGROUND: Pulmonary rehabilitation (PR) is a highly effective non-pharmacological treatment for patients with chronic respiratory diseases.OBJECTIVE: To synthesise the evidence for PR practice and efficacy in sub-Saharan Africa.METHODS: We searched in PubMed and Scopus for relevant studies and scanned reference lists of relevant studies from these databases for additional studies. Articles meeting the inclusion criteria were included. Pre-determined data were extracted independently by two reviewers. A narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…There is now a large amount of data on the long-term symptoms experienced by COVID-19 survivors after being discharged from the hospital. An Italian study that followed 143 patients 7 weeks after discharge found that 53% of patients reported fatigue, which is similar to our data, 43% reported shortness of breath, 27% reported joint pain and 22% reported chest pain [15]. In a similar study in the UK, fatigue associated with a new illness was the most common symptom, reported by 72% of participants in the intensive care group and 60.3% of participants in the ward group.…”
Section: Structure and Timing Of The Supportsupporting
confidence: 89%
“…There is now a large amount of data on the long-term symptoms experienced by COVID-19 survivors after being discharged from the hospital. An Italian study that followed 143 patients 7 weeks after discharge found that 53% of patients reported fatigue, which is similar to our data, 43% reported shortness of breath, 27% reported joint pain and 22% reported chest pain [15]. In a similar study in the UK, fatigue associated with a new illness was the most common symptom, reported by 72% of participants in the intensive care group and 60.3% of participants in the ward group.…”
Section: Structure and Timing Of The Supportsupporting
confidence: 89%
“…Participants were purposively recruited with the inclusion criteria being healthcare professionals with experience in implementing or delivering PR in LMICs. Participants were identified from papers included in two recent systematic reviews on PR in low resource settings, 14,25 and the Global RECHARGE network. 26 Recruitment emails were sent to the corresponding authors of the papers, along with a consent form, participant information sheet and request to disseminate the invitation to their colleagues.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…Participants were purposively recruited with the inclusion criteria being healthcare professionals with experience in implementing or delivering PR in LMICs. Participants were identi ed from papers included in two recent systematic reviews on PR in low resource settings 14,25 , and the Global RECHARGE network 26 . Recruitment emails were sent to the corresponding authors of the papers, along with a consent form, participant information sheet and request to disseminate the invitation to their colleagues.…”
Section: Participant Recruitmentmentioning
confidence: 99%